Diagnostic accuracy of digital thermometer compared to mercury in glass thermometer for measuring temperature in children - Periasami, Venkatesh; Naaraayan, Sridevi A.; vishwanathan, Seetha (International Journal of Contemporary Pediatrics, 2017)
Background: A wide variety of devices are available to record temperature from skin, oral or rectal mucosa and the tympanic membrane. The accuracy of different devices is varied and the primary objective of this study is to compare the diagnostic accuracy of digital thermometer against mercury in glass thermometer in children. The secondary objective was to determine the average time taken by the digital thermometer to record the temperature. Methods: This descriptive study was conducted in a pediatric ward at Institute of Child Health and Hospital for Children, Egmore, Chennai. In all 92 febrile children aged 1 month to 12 years admitted in the ward, temperature was measured at the time of admission using both digital and mercury in glass thermometers placed in each axilla after obtaining informed consent. Concordance and discordance of both measurements were determined using Pearson Correlation coefficient and Bland altman plot. Average time taken by digital thermometer to record temperature was noted. Results: There was a good correlation between mercury and digital thermometer recordings (r=0.976, p<0.001). The Bland-Altman test showed that almost all residual values (estimated-observed) are random and the fall within the 95% confidence interval. The average time taken by the digital thermometer to record the temperature was 88.03 seconds (95% CI-54.58 to 121.49). Conclusions: Digital thermometer is as accurate as mercury in glass thermometer in recording temperature. The average time taken by the digital thermometer to record temperature is 88.03 ±17.07 seconds.